"Look at Me, but Don't!" — Revisiting the Narcissistic Dilemma in Clinical Pastoral Supervision. (June 2014) - Woggon, Frank
Clinical Pastoral Education is a shame-sensitive endeavor. This article discusses the impact of shame in supervision by considering students' experiences of shame as well as the supervisor's shame and their resulting dilemmas. Exploring the paradox of shame from a psychological and theological perspective, the author suggests that shame can serve students' self-discovery, if it is engaged through pastoral confirmation and transformative interventions. Empathic attunement and humor are highlighted as effective means in such interventions.